(Table 2) Comparative growth rates of upper and lower parts of Fe-Mn nodules from the Pacific Ocean - Gleb N Baturin; Vitaly S Savenko (PANGAEA, 1989)
Dates and growth rates of iron-manganese nodules obtained by various direct and indirect methods, including radiometric, micropaleontological, geological and experimental, are discussed. Validity of assumptions, on which the radiometric dating of nodules is based and reliability of results are discussed. The problem of "buoyancy" of slow-growing nodules resting on the surface of faster-accumulating sediments is considered: It may be caused by action of deep-water fauna, bottom currents, or plastic properties of sediments.
Supplement to: Baturin, GN; Savenko, VS (1989): Growth rates of deep-water iron-manganese nodules. Oceanology, 29(3), 334-342